Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1002/jhbs.10033
|View full text |Cite
|
Sign up to set email alerts
|

Brave new worlds: Trophallaxis and the origin of society in the early twentieth century

Abstract: Trophallaxis, the process of feeding by mutual regurgitation amongst insects, was named by the North American entomologist William Morton Wheeler in 1918. I argue that entomologists, both before and after 1918, saw mutual feeding as an integral part of the behavioral whole of the nest, and moreover related its explanatory power to theories about human society. In particular, feeding behavior was seen as the key to the riddle of the origin of sociality. I show how entomologists' precise interpretations of troph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…The phenomenon received close attention as a model for the study of the origins of sociality, permeating both scientific and popular accounts of the human society during the nineteenth and twentieth centuries (Sleigh, 2002). The niche of the hymenoptera, including a subterranean way of life, large biomass density at the nest, and frequent direct individual contact, can all make them particularly vulnerable to pathogens via a fast-spread of disease among conspecifics (Kaltenpoth and Engl, 2013).…”
Section: Microbial Life and Socialitymentioning
confidence: 99%
“…The phenomenon received close attention as a model for the study of the origins of sociality, permeating both scientific and popular accounts of the human society during the nineteenth and twentieth centuries (Sleigh, 2002). The niche of the hymenoptera, including a subterranean way of life, large biomass density at the nest, and frequent direct individual contact, can all make them particularly vulnerable to pathogens via a fast-spread of disease among conspecifics (Kaltenpoth and Engl, 2013).…”
Section: Microbial Life and Socialitymentioning
confidence: 99%
“…Food exchange acts as a social bond and plays a role in developmental regulation in many social insects [e.g., termites (Isoptera), ants (Formicidae)] (e.g., Wheeler, 1911Wheeler, , 1928Raboud, 1916;Hölldobler, 1985;Hölldobler and Wilson, 1990;Melo and Campos, 1993;Hunt and Nalepa, 1994;Anderson and McShea, 2001; see Sleigh, 2002; for a history of ideas relating trophallaxis to the origins of sociality). Among bees food transfer among adults is largely restricted to the family Apidae (sensu Michener, 2000), and its social functions are especially conspicuous in corbiculate species with relatively large colonies [e.g., honeybees (Apini) and stingless bees (Meliponini)] (Moritz, 1994;Sommeijer and Bruijn, 1994;Seeley, 1995;Crailsheim, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the feeding of conspecifics and nonconspecifics by regurgitation (often termed trophallaxis in invertebrates) is a common behavior in many vertebrate and invertebrate taxa (Cammaerts, 1996;Cassill and Tschinkel, 1995;Janes, 1997;Mech et al, 1999;Pal, 2005;Rauter and Moore, 2002;Salomon et al, 2005;Schneider, 2002;Suarez and Thorne, 2000); a comparative examination of association of this type of regurgitation and gut morphology may be profitable. However, trophallaxis has not yet been reported in caterpillars of any species, perhaps because of a lack of parental care or kin selection, which appear to be key components in the evolution of trophallaxis in other invertebrate taxa such as termites, ants and honey bees (Anduaga and Huerta, 2001;Brandmayr, 1992;Sleigh, 2002). Furthermore, although some species of caterpillars do live in social groups that consist of genetically related individuals (Costa and Ross, 1993;Grant, 2005;Porter et al, 1997), behavioral mechanisms of kin bias such as trophallaxis have yet to be shown to affect colony structure (Costa, 1998;Costa and Ross, 1993;Costa and Ross, 1994).…”
Section: Discussionmentioning
confidence: 99%